Quality Management. Global Conception and Researches - Juozas Ruževičius (Amfiteatru Economic)
Quality is a concept, which cannot be measured on a time scale. Man’s understanding of quality goes far back into prehistory, perhaps even a million years before the first tools were made. For a long time quality assessment hinged predominantly on the quality of consumer products – their composition, attributes, distinguishing features, and so on. The globalization of world economy together with the expansion of international trade has led to the fast processes of quality internationalization, as a crucial element of companies’ competitiveness. These processes appear by wider application of the same methods, principles and criteria while determining quality policy, creating international accreditation, notification and quality certification systems in various countries. The development of quality management concepts covers a very long time. During this period, core quality objects have changed significantly – from quality of primitive working tools to commodities, then to services, processes, organizations’ quality and organizational performance, etc. Quality is important not only as a measure of how competitive a business is, it also determines the efficacy of state’s governance and other public sector organizations, the stability of a nation’s economy, and the quality of life its citizens enjoy. This is why it is necessary to broaden our understanding of quality, in order for other aspects (e.g. social quality, quality oriented value, quality culture, partnership, quality of economic management, etc.) to also be covered. These changes are reflected in the new book – scientific monograph in French – “Quality Management. Global Conception and Research”†, written by Juozas Ruževičius, professor at Vilnius University.